Assessment of fruit postharvest handling practices and losses in Bahir Dar, Ethiopia - Dessalegn, Yigsaw; Assefa, H.; Derso, T.; Haileslassie, Amare (Academic Journals, 2016)
Demand for fresh fruit is steadily increasing in big cities of Northwestern Ethiopia. As a result, fruits are transported from nearby as well as long distance sources to urban centers such as Bahir Dar. The type of fruit crops available in the market and number of fruit retailers are increasing from time to time. However, the key challenge facing the sector is loss across the supply chain. Therefore, the objectives of this study were to analyze fruit marketing practices, document causes and extent of postharvest losses in Bahir Dar fruit market. The study was conducted in June 2016 sing semi structured questionnaire. Thirty-one fruit retailers were randomly selected and interviewed to obtain information on their socio-economic characteristics, fruit marketing practices and postharvest losses. Data analyzed using SPSS statistical software. Results revealed that, 77.4% fruit retailers are less than 31 years old , 67.8% attended above primary school education, and 83.9% have less than six years fruit trading experience. Therefore, fruit retailers are young and educated but have very limited fruit trading experience. Of the seven fruit crops commonly sold in Bahir Dar market; mango, banana and avocado were the most prevalent. The average shelf life of fruits in retailers’ hand is only 3 to 4 days and about 20% of the fruits purchased by retailers lost before reaching to consumers mainly due to inappropriate handling and lack of proper storage facility. Therefore, multifaceted interventions such as capacity development, improved fruit production and harvesting practice, and proper storage and transportation facilities establishment are required to reduce postharvest loss and extend fruit shelf-life.